Our Virtual Tribe: Sustaining and Enhancing Community via Online Music Improvisation - MacDonald, Raymond; Burke, Robert; De Nora, Tia; Sappho Donohue, Maria; Birrell, Ross (Frontiers in Psychology, 2021)
This article documents experiences of Glasgow Improvisers Orchestra’s virtual improvisation sessions during COVID-19 pandemic via interviews with 29 participants. Sessions included an international, gender balanced, cross generational group of over 70 musicians all of whom were living under conditions of social distancing. All sessions were recorded using Zoom software . After 3 months of twice weekly two hours improvisation sessions, 29 one-hour interviews with participants were undertaken, recorded, transcribed, and analysed. Key themes include how the sessions helped participants stay connected, provided opportunities for artistic development, enhanced mood, reduced feelings of isolation, had a positive effect on mood and sustained and developed community. Particular attention is placed upon how improvisation as a universal, real time, social, collaborative process facilitates interaction allowing the technological affordances of software (latencies, sound quality, gallery/speaker view) and hardware (laptop, tablet, instruments, microphones, headphones, objects in room) to become emergent properties of artistic collaborations. The extent to which this process affects new perceptual and conceptual breakthroughs for practitioners is discussed as is the crucial and innovative relationship between audio and visual elements. Analysis of edited films of the sessions highlight artistic and theoretical and conceptual issues discussed. Emphasis is given to how the domestic environment merges with technologies to create The Theatre of Home.